2011
DOI: 10.4172/2155-9546.1000111
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic acid is a Major Component in Gonadal Fatty acids of Tropical Coral Reef fish in the Philippines and Japan

Abstract: Journal of Aquaculture Research & Development

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…With respect to the level of PUFA, almost all marine fishes in temperate and boreal seas mainly contain n-3 PUFA, while ARA is gener- tonggol PE and PC 19 , and for gonadal lipids of 24 tropical fish species 8 , a high n-6 LC-PUFA ARA and n-6 DPA found simultaneously in all polar lipids of the Epinephelinae species might be characteristic of tropical fish lipids at the coral reef. Compared with the very low levels of n-6 LC-PUFA in the northern temperate and boreal species, higher levels of ARA were found in the herbivorous fishes 21 in the coral reef.…”
Section: Lipid Content and Lipid Classes Of The Ve Epinephelinae Shesmentioning
confidence: 98%
See 1 more Smart Citation
“…With respect to the level of PUFA, almost all marine fishes in temperate and boreal seas mainly contain n-3 PUFA, while ARA is gener- tonggol PE and PC 19 , and for gonadal lipids of 24 tropical fish species 8 , a high n-6 LC-PUFA ARA and n-6 DPA found simultaneously in all polar lipids of the Epinephelinae species might be characteristic of tropical fish lipids at the coral reef. Compared with the very low levels of n-6 LC-PUFA in the northern temperate and boreal species, higher levels of ARA were found in the herbivorous fishes 21 in the coral reef.…”
Section: Lipid Content and Lipid Classes Of The Ve Epinephelinae Shesmentioning
confidence: 98%
“…Differing from the essentiality of n-3 PUFA for marine fishes 32 , the Epinephelinae species accumulate n-6 PUFA as a possible substitute for n-3 PUFA in order to maintain cell membrane fluidity. Furthermore, these n-6 LC-PUFA might be important for reproduction for the tropical fish species because high levels of n-6 LC-PUFA in gonadal lipids are often observed in many tropical fish species 8 , similar to ARA essentiality for the larvae of marine fishes 33 35 . The present study confirmed that the five Epinephelinae fish polar lipids contained markedly high levels of DHA with unusually high levels of n-6 LC-PUFA and, more specifically, that various n-6 PUFA and DHA were the characteristic fatty acids in the tissue PE and PC of the Epinephelinae fishes.…”
Section: Lipid Content and Lipid Classes Of The Ve Epinephelinae Shesmentioning
confidence: 99%
“…HUFAs are important components of cell membranes and are thought to play important roles in membrane fluidity, modulation of enzyme activity, neural development and regulation of stress resistance. Especially, (EPA: 20:5n-3) and (DHA: 22:6n-3) were considered as dietary essential FAs for normal growth and survival in most marine fish [20] . In the present study, arachidonic acid (AA) showed lower levels, 2.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, high levels of AA may be useful as a lipid biomarker of herbivorous fishes, which prefer seaweed [22] . Although C20:4 has similar biologically importance with EPA and DHA, it is often neglected in fish because it occurs only at a very low concentration, despite the possessing vital functions as the main precursor of various eicosanoids, which are produced by the ovarian tissue and play important roles in the ovulation process [20] , and cholesterol accumulation in tissues [23] , which have important roles in a variety of physiological functions including osmoregulation, cardiovascular function and the function of reproductive systems [24] . Prostaglandins plays an important role in fish reproduction [25] , with AA being the principle prostaglandins precursor involved in spawning activity of fishes, which including ovulation and sperm production [26] , and its lower levels in both sexes were probably due to its mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…ARA is always found more in PL than NL of all the tissues, probably due to its functionality in cell membrane (Alexis and Nengas, 1996;Bessonart et al, 1999;Fountoulaki et al, 2003;Furuita et al, 2003). ARA has similar biologically importance as EPA and DHA and considered as the precursor of several eicosanoids which are produced by the ovarian tissues and play an important role in the ovulation process (Venkatesh et al, 1992;Knight et al, 1995;Goetz et al, 1987;Murdoch et al, 1993;Suloma and Ogata, 2011) and cholesterol accumulation in tissues (Norambuena et al, 2012). However, EPA plays an important role in the function of eicosanoids derived from ARA as it competes with the enzyme systems producing eicosanoids from ARA, thus exerting a modulating influence over the quantity and efficacy of ARA-derived eicosanoids (Bruce et al, 1999).…”
Section: Polyunsaturated Fatty Acids (Pufa)mentioning
confidence: 99%